Pola Curah Hujan dengan Insiden Rate Demam Berdarah Dengue di Kabupaten Blitar - Lestari, Putri Dwi; Isfandiari, Muhammad Atoillah; Maryanto, Yusuf Budi (Universitas Airlangga, 2024)
Background: Dengue fever is a vector infectious disease with Aedes Aegypti mosquito as the main vector that can be found throughout Indonesia. Dengue Fever (DBD) is a health problem that exists in the world, especially in developing countries. Geographic, climatic, and population are factors that can influence the spread of vectors causing Dengue Dengue Dengue Fever disease. Objective: The purpose of this writing is to find out the relationship between rainfall and dengue fever (DBD) rate incidents. This research is a quantitative descriptive study by processing secondary data from year to year. Methods: To analyze the relationship between free variables namely dengue fever incidence rate and rainfall bound variables were conducted using the Spearman correlation test with a 95 confidence level. Instruments in this study used informed consent statements of approval for the retrieval and use of data, as well as a form of recap data on dengue fever incidence, and rainfall in every sub-district in Blitar Regency. Results: After being analyzed, it was found that for rainfall with an incident rate it has a p value of 0.432 (p> 0.05). Conclusion: This means that there is no significant relationship between rainfall and the incidence of dengue hemorrhagic fever in Blitar Regency.